Building multi-agent systems using Jason - Boss, Niklas Skamriis; Jensen, Andreas Schmidt; Villadsen, Jørgen (Annals of mathematics and artificial intelligence, 2010)
We provide a detailed description of the Jason -DTU system, including the used methodology, tools as well as team strategy. We also discuss the experience gathered in the contest. In spring 2009 the course “Artificial Intelligence and Multi-Agent Systems” was held for the first time on the Technical University of Denmark (DTU). A part of this course was a short introduction to the multi-agent framework Jason , which is an interpreter for AgentSpeak, an agent-oriented programming language. As the final project in this course a solution to the Multi-Agent Programming Contest from 2007, the Gold Miners scenario, was implemented. Finally we decided to participate in this year’s contest with an implementation made in Jason as well.